conomic theory and the New-Keynesian school - Dushko Josheski; Marija Magdinceva-Sopova (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper it is described the school of neo-Keynesians (Akerlof and Stiglitz are in the group of ”Hard” New-Keynesians, that don't accept New neo-classical synthesis, i.e. Dynamic Stochastic General equilibrium models-DSGE),that as a basic source of instability in the economies view the demand nd supply side shocks, short run is important for them, wages and prices are rigid, expectations of the economic agents are rational, but also historical data are of great importance, and they introduced microeconomic foundations for their macroeconomic models.
Keywords: E00; E12; 330; New-Keynesians; nominal rigidities; microeconomic foundations; New Keynesian model; Microfoundations